Women who kill, criminal law, and domestic abuse - McPherson, Rachel (Routledge, 2024)
"This book presents an informed, coherent and stimulating analysis of UK legal defences of homicide by victims of domestic abuse. Women killing following domestic abuse from a male partner is a significant category of homicide. In some areas of the UK it represents the most common context in which women kill. Yet, despite its significance, it is an aspect of homicide that remains under-researched within a UK context. Much of what is known about cases of this type comes from other jurisdictions. This book brings together a coherent understanding of the UK landscape in this area. It builds upon existing literature, particularly from the US, which has examined this issue from a practical perspective, using the lived experiences of practitioners involved in cases of this type. The collection combines the experiences of those in practice with academic expertise, pointing to potential sites of injustice that exist in this context and offering suggestions for reform. The volume will be a valuable guide for those involved in cases of this nature whilst also offering insight to those academics with an interest in homicide and legal responses to domestic abuse. The book will also be of interest to those working in the area of comparative criminal justice"--